PENDEKATAN EKSPOSISI DALAM PENYUTRADARAAN VIDEO FEATURE “MERAJUT ASA SEPATU LOKAL DI ERA DIGITAL” - Adibakti, Hisyam Maulana; Fadilah, Efi; Prahatmaja, Nurmaya (AT-TAWASUL, 2025)
The decreasing interest in local footwear brands in the digital era presents a major challenge for creative industries in Indonesia. The feature video "Merajut Asa Sepatu Lokal di Era Digital" was directed using an expository approach to revive the value and potential of local shoe products, especially from Cibaduyut, Bandung. Through voice-over narration, expert interviews, and illustrative footage, this work aims to reshape public perception and raise awareness among Generation Z. This study explores the application of expository directing techniques and the director’s role in constructing an informative and visually compelling narrative. The research uses participatory observation, interviews, and content analysis of the produced video. The findings indicate that the expository approach is effective in delivering social and cultural messages while strengthening visual communication in local brand imaging amidst global brand dominance